Analisis Kesalahan Berbahasa pada Teks Eksposisi dalam Platform Digital "Ruangguru" Edisi Agustus 2024 sebagai Sumber Bacaan Siswa SMA - Lutfie Juliani, Ilhas; Nabila Az-Zahra, Shinta; Maharani, Sinta; Nurul, Arizka; Muhammad Aunillah, Bagus; Abiyyu Mas’ud, Dzaka; Purwo Yudi Utomo, Asep; Galih Kesuma, Rossi (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This research is motivated by the importance of using appropriate and correct Indonesian in digital learning media, especially texts exposed oxn the “Ruangguru” platform. The purpose of this study is to identify the types of language errors contained in the exposition text and to show the causal factors that will later be used as reading material on the internet. The quality of appropriate exposition text will affect the critical ability of its readers. The research method uses a qualitative descriptive approach with the Listen and Note Technique. Data analysis uses the distribution method with the Direct Elements Technique. The results of the study show that punctuation, word choice, and word additions, with word choice errors being the most dominant. This error is caused by a lack of understanding of Indonesian rules and the influence of the use of everyday language. The benefits of improving the quality of digital education materials and increasing awareness of the importance of using Indonesian in accordance with the rules of the world of education.